Pengembangan E-LKPD Interaktif Berbasis Liveworksheet pada Materi Bangun Datar Kelas IV SD - Epa Sopiana; Atiaturrahmaniah Atiaturrahmaniah; Arif Rahman Hakim (Departement of Mathematics Education, 2023)
This study aimed to produce interactive E-LKPD products based on live worksheets on two-dimensional figure material in grade IV SD, with the number of samples used by 20 students. The method used is Research And Development (R&D), referring to the ADDIE development model (Analyze, Design, Development, Implementation and Evaluation). Based on the research that has been done, the analysis of the material validation obtained a score of 80 with the category